Implementasi Strategi LLDIKTI Wilayah X dalam Penguatan Penjaminan Mutu Program Studi Perguruan Tinggi Swasta di Kota Padang - Dhiva Nadya Maharani; Rahmadhona Fitri Helmi (Policy, Law and Political Research Center, 2026)
This study aims to analyze the implementation of the LLDIKTI Region X strategy in strengthening the quality assurance of private university study programs in Padang City. The main problem raised is the discovery of study programs with unaccredited status, expired accreditation, and inequality in quality achievement in the midst of budget limitations, human resources, and national policy dynamics. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation, and is analyzed using the Miles and Huberman interactive model. The results of the study show that the implementation of the strategy is carried out through mentoring programs, technical guidance, policy socialization, and accreditation readiness facilitation. However, the implementation has not been optimal due to budget limitations, lack of continuous monitoring and evaluation, low participation of private universities, and limited number of facilitators. However, there is an increase in the number of study programs with Excellent and Very Good ratings in the 2023–2025 period. This study concludes that the LLDIKTI Region X strategy has been running in accordance with the policy direction, but requires strengthening the aspects of evaluation, collaboration, and resource optimization so that the strengthening of quality assurance of study programs in Padang City can be achieved more effectively and sustainably.